Influence of different doses of octenidine hexafluorosilicate on parodontotium state of rat, which received cariesogenic ration - Anisimov, V. Yu. (Journal of Education, Health and Sport, 2017)
Aim: To determine of parodontium state of rat, which received cariesogenic ration and different doses of octenidine hexafluorosilicate (O-HFS). Methods: The octenidine hexafluorosilicate was synthesized by us and was used into mucoso-adgesive gels (Na-CMC) in next concentrations: 1 mg/ml, 2 mg/ml and 4 mg/ml. The rats received high-sugar cariesogenic ration and oral applications of gels with O-HFS in doses of 0,3 ml (daily doses of O-HFS were 1,4 mg/kg, 2,8 mg/kg and 5,6 mg/kg). The duration of experiment was 35 days. The activities of urease, lysozyme and elastase were determined into gum. The activities of urease, lysozyme, ALT and alkaline phosphatase (APh) were determined into serum. The degree of dysbiosis calculated by ration urease and lysozyme. The degree of atrophy of parodontale bone was determined by Nicolaeva method. Results: The activities of elastase and urease, the degree of atrophy and dysbiosis were raised into gum of rat, which received cariesogenic ration. The activities of ALT and APh, the degree of dysbiosis were raised into serum. The oral application of O-HFS-gels decreased the all these indices. The maximal action made O-HFS-gel in dose 2,8 mg/kg. Conclusion: The oral application of O-HFS-gel make parodontoprotective action.